Modified Log-BP decoding algorithm combined with PSO for Low-Density Parity Check Codes - Xiali Yan; Wenquan Feng; Qi Zhao; Hongbo Zhao (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
Message-Passing is the main decoding algorithm for Low-Density Parity Check (LDPC) Codes, in which Logarithmic Belief Propagation (Log-BP) algorithm is the most popularly used one. Particle Swarm Optimization (PSO) can also be regarded as an optimization algorithm by message-passing, which makes it possible to combine Log-BP algorithm with PSO. PSO was introduced into Log-BP algorithm by regarding all messages that bit nodes send to check nodes as the swarm with each message individually as a particle. Move the particles around in the search-space by certain iterations in each BP iteration processing, guided by the two best current values respectively found by particles themselves and that of the whole swarm. Those two best values were continually updated in each PSO iteration. In this way, the output of decoder is more consistent with accurate input sequence, in other words, the decoder performance was improved. Simulation results show that this new algorithm combined with Log-BP and PSO can get an additional 0.1 dB coding gain at Bit Error Rate (BER) of 10 -5 compared with Log-BP algorithm.